SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEBSITE PADA WENEVERWORTHLESS STORE - Muhammad Wildan Alfaruq (2021)
Employees are an important part of a company. Therefore, companies should have quality human resources in order to compete with other companies. Employee recruitment requires a Decision Support System (DSS) for employee selection that is directed at the company's goals. This research was conducted with the goal of creating a website-based decision support system application for employee recruitment at the Weneverworthless Store. Simple Additive Weighting (SAW) became the DSS method chosen because of the selection of the best alternative from several alternatives through a ranking process. The system was built using the Rapid Application Design (RAD) method. The conclusion to be obtained in this case is an application of a website-based decision support system that will be a selection tool for employee recruitment needed by the company.